Protecting women's health during the COVID-19 pandemic - Ali Mohammad Mosadeghrad (Tehran University of Medical Sciences, 2023)
The COVID-19 pandemic has damaged the lives of many people physically, psychologically, and socio-economically, and put a lot of pressure on the health system. COVID-19 infected 628.3 million people and killed 6.6 million people in the world until November 3, 2022 (1). The pandemic has exposed vast economic and social inequalities and widened the existing gap in providing services for the most vulnerable people, including women and girls. Preliminary studies show that COVID-19 disease affects men more than women. The death rate of men infected with COVID-19 is about 60 to 80% higher than that of women (2). However, as the prevalence and duration of the disease increases, its effects on women become increasingly severe. This disease undermined the fundamental rights of women and girls. They suffer disproportionately from discrimination, neglect and abuse. The World Economic Forum estimated in 2021 that the global gender gap would take about 36 years to close after the COVID-19 pandemic (3). Women make up about 70% of healthcare workers (4). Therefore, they are at higher risk of contracting the COVID-19 infection. Also, quarantine measures have led to deficiencies in sexual, reproductive and maternal health care, increased domestic violence, the increased workload of girls and women at home and their withdrawal from schools, universities and the labor market. In other words, the secondary effects of COVID-19 threaten the health and lives of women and girls.